AKULTURASI BUDAYA DALAM UPACARA KEMATIAN MASYARAKAT KOTA SANTRI KEDIRI LOMBOK BARAT (Harmoni, 2018)
This paper is aimed at understanding forms of funeral rituals and cultural acculturation in  the  procession  of  funeral  rituals  in  the society  of  the  Santri  City  Kediri,  West  Lombok. This research applies qualitative approach  that  has  starting  point  from  an  assumption  that  not  all  that  appears  is  real.  The  data  collection  is  conducted  through    observation,    interview,    and  documentation.   The   research   discovers   that, first, the customary funeral ritual is the customary ritual that has been existing since long ago before the coming of Islam, that  is  still  conducted  by  the  people  of  the  Santri  City  Kediri,  West  Lombok  up  to  this  day.  Second,  within  the  process  of  the  funeral  ritual,  there  are  several  series of rituals that must be conducted as they  are  related  each  other.  The  process  begins  from  preliminary  steps,  bathing,  shrouding,  burying,  and commemorating  the death day. Third, in the funeral ritual, the influence of custom has been existing in  the  role  and  the  cultural  acculturation  during the performance, starting from the disintermenting  to  the  religious-chanting  (dhikr) in the third to the ninth day, even to   the   hundredth   or  thousandth   day   (nyeribu).
Keywords: funeral ritual; Kediri City; Cultural acculturation; Acara Kematian; Akulturasi Budaya; Kota Kediri